<span>4(b-6)+19
Easily you would better start with distributing 4 to the brackets
4(b -6) = 4*b - 4*6 = 4b - 24
then add 19 to these terms, we get:
4b - 24 + 19
combine like terms (which are -24 + 19), we get:
4b - 5
That's it....
Hope that helps
</span>
Since the expressions for f(x) and g(x) are already given, f(g(2)) means to substitute the value of 2 to the expression of g(x), then further substituting the obtained value of g(2) into the expression of f(x). This is shown below:
f(x) = x + 8
g(x) = x^2 - 6x - 7
f(g(x) = x^2 - 6x - 7 + 8
f(g(2)) = 2^2 - 6(2) + 1
f(g(2)) = 4 - 12 + 1
f(g(2)) = -7
Therefore, the correct answer is -7.
Answer:
$1769.06
Step-by-step explanation:
The sum of Mia's three highest salaries is ...
$92,000 +94,800 +96,250 = $283,050
so the average is ...
$283,050/3 = $94,350
Her pension is then ...
0.01875 × $94,350 = $1769.06
_____
<em>Additional comment</em>
This is equivalent to the total of those salaries, divided by 160.
T/3 × 0.01875 = T × (0.01875/3) = T × 0.00625 = T/160
Sometimes, there are simpler ways to calculate things like this.
I don't know if u can see it, but there.
X=12
Y=15
Z=20